2016
DOI: 10.1136/bmjspcare-2015-000956
|View full text |Cite
|
Sign up to set email alerts
|

Education and training to enhance end-of-life care for nursing home staff: a systematic literature review

Abstract: BackgroundThe delivery of end-of-life care in nursing homes is challenging. This situation is of concern as 20% of the population die in this setting. Commonly reported reasons include limited access to medical care, inadequate clinical leadership and poor communication between nursing home and medical staff. Education for nursing home staff is suggested as the most important way of overcoming these obstacles.ObjectivesTo identify educational interventions to enhance end-of-life care for nursing home staff and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
74
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(81 citation statements)
references
References 31 publications
6
74
0
1
Order By: Relevance
“…Changes to patient and family related policies were a direct result of the educational intervention in two other studies (Curry et al, ; Phillips et al, ). Innovative methods of assessment are needed to ensure that outcomes of palliative educational interventions are not limited solely to perceptions of improved care but are indeed measureable and meaningful improvements for patients living with life‐limiting chronic illness (Anstey et al, ; Karacsony, Chang, Johnson, Good, & Edenborough, ; Pesut & Greig, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Changes to patient and family related policies were a direct result of the educational intervention in two other studies (Curry et al, ; Phillips et al, ). Innovative methods of assessment are needed to ensure that outcomes of palliative educational interventions are not limited solely to perceptions of improved care but are indeed measureable and meaningful improvements for patients living with life‐limiting chronic illness (Anstey et al, ; Karacsony, Chang, Johnson, Good, & Edenborough, ; Pesut & Greig, ).…”
Section: Discussionmentioning
confidence: 99%
“…Finally, determining if an educational intervention has statistically improved communication, teamwork, practice, patient care or care of family members is challenging (Anstey, Powell, Coles, Hale, & Gould, 2016;Pesut & Greig, 2017;Raunkiaer & Timm, 2013). Most authors reported what the participants perceived as outcomes for patients and families.…”
Section: Suggestions For Managers Who Are Contemplating a Collaboramentioning
confidence: 99%
“…The principle threat to implementing NP, in our view, is inadequate knowledge and incompetence, which can be addressed effectively through mainstreaming, effective continuing education program [75] and application of Benner's stages of clinical competence [16][17][18].…”
Section: Resultsmentioning
confidence: 99%
“…This resolution called upon World Health Organisation (WHO) and Member States to improve access to palliative care as a core component of health systems. Good end‐of‐life care demonstrates that patients and their families are being treated with kindness, respect and empathy, and helps those approaching death to remain comfortable (Anstey, Powell, Coles, Hale, & Gould, ). When distressing symptoms are managed, patients are more likely to die with dignity and their families are more likely to be satisfied with the care received (Teno et al, ).…”
Section: Introductionmentioning
confidence: 99%